Basil Bernstein’s pedagogic device : a constructive tool for the knower - Kimberly Ann Adams 1983- (2020)
Throughout this paper, I have explicated a process of recontextualization in two ways: one, relating the International Studies in Education program (ORF), into the Educational Settings Course (PRF); and two, this paper itself, relating the elaborated codes of Basil Bernstein’s Pedagogic Device, into a general code for audiences that are still learning. Due to the height of Bernstein’s elaborated code, many of the students found his work complex and incomprehensible. This gave me the incentive to create a final project that would encompass more mundane texts, without losing the epistemological context, incorporating common experiences from the International Studies in Education Program, to function as common knowledge, a workable source that all students can see themselves in and relate to. In other words, I will create a student’s perspective and approach to understanding Bernstein’s Pedagogic Device. This process was not only a realization of Bernstein’s theory but also a true test of my recognition of his concepts. They allowed me to actively reflect about prior knowledge, what I had accumulated when I entered the ISE Program in 2017, with the higher-level understanding that I have now as I finish the program. I was able to recognize Bernstein on my own early on. He had immediate meaning and value for me in my academic passage. With each effort to include Bernstein in some extent in my own settings as I developed these to incorporate his ideas into my experiences. As an international student of the International Studies in Education Program here at the University of Iceland, I understand and appreciate the true value of socio-cultural transmission, and it gives me the power to share my knowledge for a greater good to the knower.